Growth and Production of Cassavas in Intercropping System with Cowpeas - Sinaga, Intan Lorenza; Suwarto, Suwarto; Purnamawati, Heni; Guntoro, Dwi (Department of Agronomy and Horticulture, IPB University, 2024)
Cassava is one of the most important commodities worldwide, serving as a crucial food source due to its rich content of nutrients such as carbohydrates, protein, fat, calcium, and magnesium. Cassava is a perennial crop with slow growth, necessitating the selection of intercrops with shorter harvest periods. Cowpea, a legume high in protein, is widely cultivated and suitable for intercropping with cassava. Intercropping these crops involves adjusting planting distances to optimize yield. This study aims to determine the optimal planting distance in an intercropping system that yields the highest productivity for the cassava variety “Mangu” and the cowpea varieties “Albina” and “Uno”. The research was conducted from January to June 2023 at the IPB Experimental Farm in Sawahbaru, Dramaga, Bogor, on Latosol soil, at an altitude of 207 meters above sea level. The study utilized a randomized complete block design with a single factor: the intercropping system pattern. The patterns tested were 1:2 (one row of cassava with two rows of cowpea) and 1:3 (one row of cassava with three rows of cowpea), consisting of: P1: “Mangu” and “Uno” 1:2; P2: “Mangu” and “Uno” 1:3; P3: “Mangu” and “Albina” 1:2; P4: “Mangu” and “Albina” 1:3; P5: “Mangu” monoculture; P6: “Uno” monoculture; P7: “Albina” monoculture. The results indicated that the P3 planting system yielded the highest crown height at 1, 5, and 6 months after planting (MAP), the highest canopy diameter at 4 months after planting, tuber production, and 100 seed weight of cowpea. The P4 system produced the highest stem diameter, number of leaves, number of pods, pod dry weight, and seed dry weight at 9 months after planting.